A new insight into promotion action of Co2+ in Ni-diamond composite electrodeposition. Issue 8 (August 2019) - Zhou, Haifei; Du, Nan; Guo, Jingdong; Liu, Shuan
Graphical abstract: Highlights: Addition of Co 2+ in Watt's bath remarkably increased the content of particles in deposits for Ni-diamond system. The cathodic zero potential has a significant effect on the entry of particles into coatings. Addition of Co 2+ can not only increase Faraday resistance but also reduce reduction rate of metallic cations. Physical model of diamond particles deposition state before and after the addition of Co 2+ was established. Abstract: A new insight into the promotion action of Co 2+ on both particle and metal deposition in Ni-diamond composite electrodeposition system was analyzed according to electrochemical measurements. The results showed that the addition of Co 2+ made particles content in deposits increased remarkably. The change of particles content in deposits was related inversely to the change of cathodic zero potential with the increase of the concentration of cobalt sulfate. Zero charge potential of cathode was shifted to much more negative region. The negative shift of the zero potential, combining with positive shift of the zeta potential, increased the electrostatic force between the particle-adsorbed metallic cations and the cathode. It not only benefits to the transportation of particles in solution towards cathode, but also shortens their residence time on cathodic surface. Meanwhile, entry of particles is also promoted. For metals deposition, reduction resistance of metallic cations rises greatly and deposition current at cathodic potentiodynamic polarization decreases after cobalt sulfate has been added into electrolyte. These factors are favorable for increasing particles content in deposits. In addition, physical model of diamond particles deposition state before and after the addition of Co 2+ has been discussed.